2011
DOI: 10.1210/jc.2010-2693
|View full text |Cite
|
Sign up to set email alerts
|

The Thyroid Epidemiology, Audit, and Research Study (TEARS): Morbidity in Patients with Endogenous Subclinical Hyperthyroidism

Abstract: Patients with endogenous SH have an increased risk of cardiovascular disease and dysrhythmia. There is an association with fracture and dementia that is not related to TSH concentration and therefore is less likely to be causally related. No association was found between SH and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
127
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 21 publications
5
127
0
6
Order By: Relevance
“…Endogenous subclinical thyrotoxicosis has been associated with atrial fibrillation in multiple studies, with the risk proportional to the degree of TSH suppression (19)(20)(21)(22)(23)(24). This increased risk of atrial fibrillation appears to be similar when thyrotoxicosis stems from overtreatment with thyroid hormone supplementation (22).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous subclinical thyrotoxicosis has been associated with atrial fibrillation in multiple studies, with the risk proportional to the degree of TSH suppression (19)(20)(21)(22)(23)(24). This increased risk of atrial fibrillation appears to be similar when thyrotoxicosis stems from overtreatment with thyroid hormone supplementation (22).…”
Section: Introductionmentioning
confidence: 99%
“…Both overt hypothyroidism and hyperthyroidism have been associated with increased risk of fractures in previous studies (6,7,8,9,10,11,12,13,14). Other studies have reported that fractures are more common in persons with subclinical thyroid dysfunction (15,16), and some have found fracture incidence to increase by decreasing thyroid-stimulating hormone (TSH) within the reference range (13,17,18). However, the results of these and other studies are inconsistent (7,13,14,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…SCH has been found to be associated with a higher risk of atrial fibrillation, hypertension, osteoporosis, and dementia compared with euthyroid subjects in some (3,4,5,6) but not all (7,8,9) studies. Similarly, the findings from the cohort studies on the association between SCH and cardiovascular disease (CVD), cardiovascular, and all-cause mortality were also inconsistent (10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27). Lack of randomized clinical trials answering the question whether long-term health outcomes are improved by treatment of SCH made this issue more elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Since the latest meta-analysis had been performed (31), the interest of researchers on this issue rose. A total of 11 new large prospective studies (17,18,19,20,21,22,23,24,25,26,27) on this issue have been published. Now data are sufficient to update the meta-analysis to provide more powerful evidence for physicians and policy-makers.…”
Section: Introductionmentioning
confidence: 99%